LEARNING STRATEGIES USED BY ENGLISH DEPARTMENT STUDENTS IN LEARNING PRONUNCIATION (RETAIN, 2016)
LEARNING STRATEGIES USED BY ENGLISH DEPARTMENT STUDENTS IN LEARNING PRONUNCIATION Hermin Dwi Wulandari English Department, Faculty of Languages and Arts, State University of Surabaya. herminwulandari@mhs.unesa.ac.id Lies Amin Lestari English Department, Faculty of Languages and Arts, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Sebagian besar siswa bahkan mahasiswa Indonesia memiliki kesulitan untuk melafalkan bahasa Inggris dengan tepat. Maka, diperlukan adanya strategi yang tepat untuk mempelajari pelafalan bahassa Inggris dengan tepat. Penelitian terdahulu telah menyebutkan bahwa siswa yang berprestasi menggunakan strategi belajar cognitive melalui kegiatan menonton TV, mendengarkan musik, menggunakan kamus, dll, serta strategi metacognitive melalui memperhatikan secara seksama bagaimana bahasa Inggris dilafalkan dengan benar. Maka, diperlukan untuk menggali lebih dalam tentang proses yang rinci dari strategi-strategi tersebut karena penelitian terdahulu hanya menyebutkannya secara umum. Pertanyaan yang muncul adalah : 1. Strategi apa yang digunakan mahasiswa utnuk belajar pelafalan bahasa Inggris? 2. Bagaimana strategi tersebut membantu mahasiswa untuk menguasai pelafalan bahasa Inggris? 3. Bagaimana pendapat mahsiswa tentang keefektifan strategi yang mereka gunakan dalam belajar pelafalan bahasa Inggris? Penelitian ini termasuk penelitian kualitatif dimana interview dilakukan untuk mendapatkan data. Hasil yang didapat menunjukkan bahwa siswa memiliki strategi yang bervariasi dalam mempelajari pelafalan bahasa Inggris yang dikategorikan dalam taksonomi Oxford. Masing-masing strategi memberikan pelajaran dan manfaat. Siswa juga berpendapat bahwa strategi terbaik dalam belajar pelafalan bahasa Ingris adalah melalui pembicara asli dan diskusi dengan orang lain Kata Kunci: pelafalan, strategi belajar Abstract Most of Indonesian students, even college students, got difficulty in pronouncing English pronunciation. Then, it is necessary find out the best strategy to learn pronunciation, so it can the model or guidance for others to learn English pronunciation. A previous study mentioned that good language learners used cognitive strategy such as, watching movie, listening to music, checking dictionary, etc and metacognitive strategy through paying attention on how English words are pronounced (Mulyani, Haryanto & Dollah, 2014). Therefore, it is necessary to know the detail process of the strategies used in learning pronunciation because the previous research just listed it very generally. The questions are formulated as follows: (1) What strategies are used by English Department students in learning pronunciation? (2) How do learning strategies help English Department students to master English pronunciation? (3) How are the students’ perspectives of the effectiveness of strategies used? Qualitative research is used in which interview is conducted to get the data. The result showed that the students used various strategies categorized in Oxford’s taxonomy. Each strategy gives different exposure depending on the opportunity and advantages given by applying the strategies. Then, the students argued that the best strategy in learning pronunciation are through learning from native speakers and practicing by discussion with others. Keywords: English pronunciation, strategy